Designing by decorating: The use of pictures in primary school - Lundh, Anna Hampson; Limberg, L. (University of Sheffield, 2012)
Introduction. This paper concerns the concept of information use. The aim of the study is to understand how information use, as an activity, is shaped when project-based methods are used in primary school. The particular focus here is information use which involves visual information resources. It relates to the overarching aim of a set of studies describing and illustrating how information literacies are enacted and socially shaped in Swedish primary schools. Method. 25 booklets, produced by children at a Swedish primary school when working with project-based assignments, were collected during an ethnographical study. Analysis. An analysis of the relationships between pictures and text in the 25 booklets was conducted. Results. The analysis suggests that the pictures in the booklets are subordinated to written text and their functions are decorative and illustrative. Pictures are seldom used for explaining or narrating. Conclusions. An underpinning idea of the study is to understand information activities as purposeful within the settings where they take place. Given earlier research indicating that project-based working methods tend to be focused on the reproduction of facts and the making of products rather than on contents, it could be argued that the children's use of pictures in this study is purposeful. However, if this use of pictures is a desirable outcome could be a matter of discussion. The findings may be relevant for developing teaching in the multimodal aspects of information use.